Finding success with soybeans [Uganda] - Wanyoto, Anthony (Technical Centre for Agricultural and Rural Cooperation, 2018)
In northen Uganda, one cooperative has benefitted from the second phase of the Vegetable Oil Development Project, which has given its members access to training, improved seeds and guaranteed markets. By boosting soybean production, the project is also increasing the supply of oilseeds for Ugandan processors.